Short report on the excavations at the site Makó – Igási Ugar - Váczi, Gábor; Bartus, Dávid (Dissertationes Archaeologicae, 2013)
The Institute of Archaeological Sciences, Eötvös Loránd University carried out preventive excavations at the site Makó – Igási Ugar in the frame of the highway construction works of section “M43 Makó – Csanádpalota” in 2012–2013, where traces of a settlement from the 12th century were found.